Genetic Variation of At-Hook Transcription Factor (Akna) Rs3748178 is Associated with the Relapse of Graves’ Disease - Dwi Anita Suryandari (Journal of Global Pharma Technology, 2019)
Objective: As many as 30-60% of patients with Graves' disease (GD) have relapsed after antithyroid withdrawal, which may be caused by genetic variation of susceptibility factors. This study aimed to analyze the genetic variation of AT-hook transcription factor AKNA rs3748178 and its association with relapse in Graves' disease patients.Methods: This research was a case-control study examining 60 DNA samples of GD patients, who were equally allocated into relapse and remission groups. Genetic variation was analyzed with PCR-RFLP. Fisher's exact test was used for statistical analysis and a p-value less than 0.05 was considered significant.Results: The proportion of patients who experienced a relapse with homozygote wild type (n= 27, 90%) was significantly higher (p= 0.015) compared to the heterozygote and homozygote mutant (n=3, 10%). Graves’ disease patients with GG genotype were more likely to have a relapse (OR 6.00, 95% CI 1.48–24.3, p= 0.015). The proportion of patients who experienced a relapse with G allotype (95%) was significantly higher (p= 0.004) compared to A allotype (5%). Graves’ disease patients with G allotype were more likely to have a relapse (OR 6.33, 95% CI 1.73–23.2, p= 0.004).Conclusions: Genetic variation of AT-hook transcription factor AKNA rs3748178 is associated with relapse in GD patients.Keywords: Graves’ disease, recurrence, genetic variation